PEMANFAATAN SENYAWA KOMPLEKS FE KELAT (EDTA, DTPA, EDDHA, AMINO) DALAM BIDANG PERTANIAN: SEBUAH TINJAUAN - Hanisah Hasibuan; Anjany Tasya Br Tarigan; Iis Siti Jahro; Nurfajriani (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2025)
This study discussed the use of iron (Fe) complex compounds in the form of chelates such as EDTA, DTPA, EDDHA, and amino chelates to overcome Fe deficiency in plants. Fe deficiency often occurs in soils with high pH or calcareous soils, which can be seen from chlorosis in leaves and decreased productivity. This study was aimed to review the synthesis, stability, agronomic effectiveness, and environmental impact of various types of Fe chelates. The methods used in this study were literature studies, with data sources covering articles from 2016 to 2025, with a particular focus on articles discussing the use of Fe chelates in plants. The findings of this study indicated that Fe-EDTA works well at low to moderate pH levels but is less stable in alkaline soils. Fe-DTPA showed moderate stability up to pH 7, while Fe-EDDHA had high stability even at pH 9, making it more suitable for calcareous soils. More environmentally friendly alternatives such as Fe-amino chelates have been proven to be more easily absorbed, have a positive impact on the environment, and also function as biostimulants. Therefore, further research is recommended to explore the development of environmentally friendly and effective Fe-chelates in alkaline soils to reduce residues from synthetic materials.